2010 IEEE Conference on Innovative Technologies for an Efficient and Reliable Electricity Supply 2010
DOI: 10.1109/citres.2010.5619781
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of plug-in hybrid electric vehicles on the electric power system in Illinois

Abstract: Future impacts on the electric power system in Illinois due to additional load from plug-in hybrid electric vehicles (PHEVs) are analyzed. The operation of the state's electric power system was simulated under a baseline scenario (i.e., without PHEVs) and three scenarios with PHEVs. The latter scenarios assumed different time periods throughout the day when PHEVs would be charging. The study assumed that PHEVs comprised 10% of the total number of light-duty vehicles on the road in 2020. Results of the simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In [7], Mahalik et al, carried out a study of impacts on the electric system of the State of Illinois, located in the Midwest of the US. This work is evaluated in a similar way to [6], assessing the future impacts due to additional load that represent the connection of EVs.…”
Section: "Electric Vehicle" and Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7], Mahalik et al, carried out a study of impacts on the electric system of the State of Illinois, located in the Midwest of the US. This work is evaluated in a similar way to [6], assessing the future impacts due to additional load that represent the connection of EVs.…”
Section: "Electric Vehicle" and Planningmentioning
confidence: 99%
“…In [8], Poch et al, applied a similar methodology to the one presented in [7], but in the West of US. Moreover, the obtained results on the impacts of the connection of EVs are lightly different.…”
Section: "Electric Vehicle" and Planningmentioning
confidence: 99%
“…This can be brought down to 7 Euro cents/KWh with off-peak charging and with higher renewables and low general costs, down to 5.6 Euro cents/KWh. Mahalik et al [14] performed a simulation to realize EV impacts on the Illinois grid in 2020 and concluded that on-peak uncontrolled charging would require an additional 400 MW unit to support the state's reserve margin. If off-peak and controlled charging is facilitated, no additional supporting grid would be needed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It revealed that every 10% increase of EV penetration created an 18% increase in maximum demand when uncontrolled charging had taken place. On the other hand, an impact study on the electricity grid in Illinois [27] concluded that the total increment in network load would be 0.8% for a maximum EV market penetration of 10%, by 2020. It confirmed that an addition of 400 MW generation to the grid would be sufficient even if EVs tended to charge on-peak.…”
Section: Impact On Supply and Demand Balancementioning
confidence: 99%